DOI: 10.11606/d.55.2012.tde-05122012-095421
|View full text |Cite
|
Sign up to set email alerts
|

Uma abordagem baseada em técnicas de visualização de informações para avaliação de características de imagens e aplicações

Abstract: A minha mãe Clara pelo amor incondicional e a meu tío Jesús pelo valioso apoio. v Agradecimentos Agradeço primeiro a Deus pela oportunidade deste crescimento de vida e pela força que me deu durante todo este tempo. Agradeço principalmente a minha mãe pelo apoio recebido, meu exemplo a seguir, com ela aprendi todo o valor desta vida. A meu pai, a minha avô, minhas tías, meus tios e primos pelo apoio incondicional oferecido durante toda minha formação. Sem vocês nada seria possível. Agradeço à professora Rosane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Some studies focus on classification problems, such as those by Zhang et al (2016b), Yang and Moody (2000), Botelho (2011) and Cruz (2012). The visualization system by Zhang et al (2016b) supports users to inspect and direct the variable selection in decision trees.…”
Section: Visualization and Analysis Of Variables In Connection With Smentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies focus on classification problems, such as those by Zhang et al (2016b), Yang and Moody (2000), Botelho (2011) and Cruz (2012). The visualization system by Zhang et al (2016b) supports users to inspect and direct the variable selection in decision trees.…”
Section: Visualization and Analysis Of Variables In Connection With Smentioning
confidence: 99%
“…Results have shown that this approach for variable selection allows determining variable subsets capable of generating improved projections in terms of visual quality. Also handling image collections, Cruz (2012) uses Neighbor Joining (NJ) similarity trees to select, evaluate and compare variables spaces. The similarity tree generated from the variables allows the user to select a variable space that maintains or improves the quality of the visualizations of the image set.…”
Section: Visualization and Analysis Of Variables In Connection With Smentioning
confidence: 99%
See 1 more Smart Citation